Horizontal traumatic laceration of the pancreas head: A rare case report. (2017) - Nanashima, Atsushi; Imamura, Naoya; Tsuchimochi, Yuki; Hamada, Takeomi; Yano, Kouichi; Hiyoshi, Masahide; Fujii, Yoshiro; Kawano, Fumiaki; MitsuruTamura
Highlights: A woman involved in a car crash sustained blunt pancreatic head trauma that resulted in hemorrhagic shock. A rare horizontal laceration and complete transection of pancreatic head was discovered during surgery. The main pancreatic duct was not injured. The lower part of the pancreatic head including the uncus and attached duodenum was partially resected and the remnant duodenum was anastomosed with the Roux-en Y limb of the jejunum by functional side-to-side anastomosis. The patient recovered without developing major complications. Abstract: Introduction: This case report is intended to inform acute care surgeons about treating rare horizontal laceration of the pancreas head caused by blunt trauma. Case presentation: A 57-year-old woman who sustained blunt abdominal trauma during a car crash was transported to the emergency center of our hospital with unstable vital signs due to hemorrhagic shock. Computed tomography showed transection of the pancreas head and massive intra-abdominal hemorrhage. She was referred for emergency surgery because of a transient response. Laparotomy at five hours after the accident initially revealed consistent massive bleeding from branches of the superior mesenteric artery and vein, which we resolved by suturing the vessels without damaging the main trunks. A horizontal laceration and complete transection of the pancreatic head were then confirmed but the main pancreatic duct remained intact. The lower part of the pancreatic head including the uncus with the attached part of the duodenum was resected, and the pancreatic stump remaining after transection was fixed by suturing. The jejunal limb was attached to the remnant duodenum by side-to-side functional anastomosis. Although gastric emptying was delayed for one month after surgery, the postoperative course was good and the patient recovered at three months thereafter. The embryonic border of pancreas head accompanied with pancreatic divisum was considered for this laceration without disruption of the main pancreatic duct. Discussion: Blunt pancreatic trauma usually causes vertical transection and thus, horizontal transection is considered rare. The embryological anatomical border between the ventral and dorsal pancreas due to pancreatic divisum was supposed to be transected and therefore the main pancreatic duct was not damaged. Conclusion: Hemorrhagic shock and rare pancreatic head trauma were treated by appropriate intraoperative management.